Coping Mechanisms and Social Support To Reduce Nurse Students' Anxiety In Facing Competency Tests - Fitriani, Dwi Rahmah; Allison, Enda Maimia Taesa; Aldi, M; Wahyuni, Tri; Damaiyanti, Mukripah (Media Keperawatan Indonesia, 2025)
Nursing students who will face competency tests generally have varying levels of anxiety and this will likely have an impact on the competency test results. The aim of this research is to analyze the relationship between coping mechanisms and social support with the level of anxiety of nursing students in facing competency tests in Samarinda. This research uses quantitative research methods with a cross-sectional design. There were 138 respondents in this study using total sampling technique. Data was collected using the Brief Cope questionnaire for coping mechanisms, social support using the Multidimensional Scale of Perceived Social Support and the State Anxiety Inventory for anxiety. The results of the analysis of the independent and dependent variables using the gamma correlation test were obtained for coping mechanisms with an anxiety level of P value: 0.312 and social support with an anxiety level of p value of 0.015. So it was found that there was a relationship between social support and the level of anxiety in nursing students who were facing competency exams in Samarinda City.